1999
DOI: 10.1021/cm9807687
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen as a Reactive Intermediate in the Photodegradation of Phenylenevinylene Oligomers

Abstract: Singlet molecular oxygen (a1Δg) is shown to be the principal reactive intermediate in the photoinduced oxygen-dependent decomposition of a series of phenylenevinylene oligomers. The reaction rate between singlet oxygen and the oligomer decreases (1) with a decrease in the extent of phenylenevinylene conjugation (i.e., oligomer chain length) and (2) upon the incorporation of electron-withdrawing substituents on the oligomer. The reaction rate, however, does not appear to depend solely on the electron density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 42 publications
5
76
0
Order By: Relevance
“…Since electroluminescence is normally only observed from the shortlived singlet excited state, long-lived triplet states may also act as traps to reduce the concentration of these species in devices [23]. Secondly, in the presence of molecular oxygen, triplet states may sensitise the formation of singlet oxygen, which can react with polymer chains, and ultimately limit device performance and lifetime [23][24][25][26][27]. On the beneficial side, the electronic energy from the triplet states of these systems may, however, be captured by appropriate acceptors, and these systems show potential as electrophosphorescent devices [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Since electroluminescence is normally only observed from the shortlived singlet excited state, long-lived triplet states may also act as traps to reduce the concentration of these species in devices [23]. Secondly, in the presence of molecular oxygen, triplet states may sensitise the formation of singlet oxygen, which can react with polymer chains, and ultimately limit device performance and lifetime [23][24][25][26][27]. On the beneficial side, the electronic energy from the triplet states of these systems may, however, be captured by appropriate acceptors, and these systems show potential as electrophosphorescent devices [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Then, this singlet oxygen molecule attacks the chemical bonds of the polymer. The long lifetime of the triplet state of MEH-PPV (~100 μs in deoxygenated solution 33 ) provides enough time for such a reaction to occur.…”
Section: Resultsmentioning
confidence: 99%
“…This degradation continues until the device fails [2,3]. Studies have shown that substitution with electron withdrawing or donating substituents can alter the rate of degradation of electroluminescent polymers [4,5,6]. It has been found that substitution with electron donating alkyloxy side chains increases the rate of degradation of the polymer [4], while phenyl or cyano electron withdrawing substituents lead to a decrease in the rate of degradation, particularly if the substituent is placed on the vinylene bonds [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that substitution with electron withdrawing or donating substituents can alter the rate of degradation of electroluminescent polymers [4,5,6]. It has been found that substitution with electron donating alkyloxy side chains increases the rate of degradation of the polymer [4], while phenyl or cyano electron withdrawing substituents lead to a decrease in the rate of degradation, particularly if the substituent is placed on the vinylene bonds [5,6]. Trifluoromethyl substituted compounds have been shown to be particularly stable towards photo-oxidation accentuating the benefit of electron deficient vinylene linkages and pointing towards the vulnerability of this moiety to degradation [7].…”
Section: Introductionmentioning
confidence: 99%